POLA KOMUNIKASI PELAYANAN DAN PEMBERIAN INFORMASI KESEHATAN PADA PUSKESMAS KADUHEJO KABUPATEN PANDEGLANG - Muchsinin Ichsan Ismail; Titi Stiawati; Ipah Ema Jumiati (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2023)
This study aims to determine the communication patterns of health services and information at the Kaduhejo Community Health Center, Pandeglang Regency, along with the obstacles. The object of research is the pattern of service communication and provision of health information. This study used qualitative research methods. Data collection techniques were carried out through observation, interviews, and literature. The procedure in the qualitative analysis process consists of three main activities that are interrelated and occur simultaneously, namely data reduction, data presentation and drawing conclusions. The results of his research showed that the pattern of service communication and providing health information at the Kaduhejo Health Center in Pandeglang Regency was more dominant using a linear communication pattern. The inhibiting factor in implementing the communication pattern is due to technical, semantic and human factors.